A Case of Yersinia Infection from the Middle East: Case Report and Literature Review - Ahmed Baraka; Talib Juma; Suad Al-Alousi; HA Sheikh; Sami Asfar (Canadian Journal of Gastroenterology)
The authors report the first case of yersinia infection of the cecum, appendix and mesenteric lymph nodes from the Middle East, together with a literature review on yersiniosis. The case is unique in that the cecum was affected while the terminal ileum was free from disease.